Improving Persuasive Science Writing for Secondary Students With Emotional and Behavioral Disorders Educated in Residential Treatment Facilities. (August 2019) - Garwood, Justin D.; Werts, Margaret G.; Mason, Linda H.; Harris, Bronwyn; Austin, Morgan B.; Ciullo, Stephen; Magner, Karen; Koppenhaver, David A.; Shin, Mikyung
Many students who have experienced complex trauma receive special education services related to emotional and behavioral disorders at residential treatment facilities (RTFs) as they undergo therapy. One academic skill in which students with emotional and behavioral disorders often struggle is writing. The current multi-probe, multiple-baseline, across-groups-of-students study involved a science teacher in an RTF delivering whole-class persuasive writing instruction using the self-regulated strategy development model with 11 secondary students experiencing complex trauma. Results suggested large effects for persuasive parts (overall Tau- U = .97), word count (overall Tau- U = .96), and holistic quality (overall Tau- U = .97), as well as high social validity among participants. Implications for providing instruction to students in RTF settings and future directions for this population are included.